2015
DOI: 10.2334/josnusd.57.373
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the gonial angle on lateral cephalometric radiographs and panoramic radiographs

Abstract: We measured the gonial angle (GA)on panoramic radiography (PR) and analyzed the correlation between the GA on PR and lateral cephalometric radiography (LCR). In total, 49 PR films and LCR films from dentate young adults were evaluated. Orthodontists plotted four points (articulare, menton, posterior gonion, and lower gonion) on the PR and carefully traced them. Using a protractor, two radiologists measured the GA on LCR images. A simultaneous experimental study of two dry skulls was performed to compare the GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 44 publications
0
10
1
4
Order By: Relevance
“…Shahabi et al13 compared the external gonial angle determined using lateral cephalograms and panoramic radiographs of class I patients and concluded that panoramic radiography could be used for determining the gonial angle as accurately as a lateral cephalogram. Araki et al,14 in 2015, compared the gonial angles measured using 49 panoramic radiographs with the gonial angle estimated using lateral cephalometric radiographs taken from 2 dry mandibles and found that the gonial angle measurements were slightly smaller on the panoramic radiographs than on the lateral cephalometric radiographs. Alhaija et al15 evaluated the potential of panoramic radiographs to measure mandibular inclination and steepness; they observed a high correlation between the measurements taken using both types of radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…Shahabi et al13 compared the external gonial angle determined using lateral cephalograms and panoramic radiographs of class I patients and concluded that panoramic radiography could be used for determining the gonial angle as accurately as a lateral cephalogram. Araki et al,14 in 2015, compared the gonial angles measured using 49 panoramic radiographs with the gonial angle estimated using lateral cephalometric radiographs taken from 2 dry mandibles and found that the gonial angle measurements were slightly smaller on the panoramic radiographs than on the lateral cephalometric radiographs. Alhaija et al15 evaluated the potential of panoramic radiographs to measure mandibular inclination and steepness; they observed a high correlation between the measurements taken using both types of radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…Araki et al . [ 7 ] in his study, found that the gonial angle measurements were slightly smaller on the panoramic radiographs than on the lateral cephalometric radiographs.…”
Section: Discussionmentioning
confidence: 94%
“…This was because in the posterior and lateral aspects of the mandible, the angular values are not influenced by image distortion inherent with panoramic radiography. In a most recent study, Araki et al 21 in 2015 compared gonial angles measured from 49 panoramic radiographs with the gonial angle on lateral cephalometric radiographs taken for 2 dry mandibles. The gonial angle measurements were slightly smaller on the panoramic radiographs than on the lateral cephalometric radiographs.…”
Section: Discussionmentioning
confidence: 99%